Anmeldelser - Tvarnø Lind, Tore (Danish Yearbook of Musicology, 2012)
Review of: Mark Slobin: Folk Music: A Very Short Introduction. Oxford & New York: Oxford University Press, 2011. Very Short Introductions, vol. 257.